2015
DOI: 10.1590/s0102-865020150070000002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote ischemic preconditioning in the expression of IL-6 and IL-10 in a rat model of liver ischemia-reperfusion injury

Abstract: PURPOSE:To study the effect of remote ischemic preconditioning (RIPC) in ischemia-reperfusion (I/R) liver injury and in the expression of IL-6 and IL-10 in a rat model. METHODS:Thirty-six male rats were divided in three groups: Sham; I/R injury, a 45 minutes lobar liver ischemia and reperfusion; and RIPC, six cycles of four minutes of ischemia and four minutes of reperfusion on the right hindlimb followed by a 45 minutes lobar liver ischemia and reperfusion. Tissue and blood samples were collected after 1h and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…RIPC has been shown by our own group and others to ameliorate hepatic IR injury in small animal models 12,13,14,15 . It has also been translated into clinical benefit in patients undergoing both cardiac surgery 16 and major vascular surgery 17 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…RIPC has been shown by our own group and others to ameliorate hepatic IR injury in small animal models 12,13,14,15 . It has also been translated into clinical benefit in patients undergoing both cardiac surgery 16 and major vascular surgery 17 .…”
Section: Discussionmentioning
confidence: 91%
“…RIPC has been shown by our own group and others to ameliorate hepatic IR injury in small animal models 12,13,14,15 . It has also been translated into clinical benefit in patients undergoing both cardiac surgery 16 The aims of this study was to perform a prospective randomized controlled feasibility study to address these issues and to obtain preliminary data on which to design a further prospective trial to determine efficacy and cost effectiveness.…”
mentioning
confidence: 91%
“… have demonstrated that remote IPC on the limbs results in favourable changes in mitochondrial oxygenation, serum bicarbonate and hepatic venous nitric oxide (NO), NO protects against MPT‐dependent apoptosis through the cGMP‐dependent kinase signalling pathway . One study has executed IPC in the right hind limbs of rats with six cycles of pre‐condition clamping and reperfusion and has found that the attenuated liver necrosis is mediated by the up‐regulation of interleukin(IL)‐6 . In addition to remote IPC on limbs, intestinal IPC has also eliminated hepatic IR‐induced injury by decreasing inflammatory cytokines and enhancing Bcl‐2 expression .…”
Section: Ipc For Attenuating Hepatic Ir Injurymentioning
confidence: 99%
“…RIPC induced HO-1 expression in several organs, but not in the skin. Interestingly, HO-1 can also promote regeneration in a paracrine fashion via its versatile effector molecules biliverdin/bilirubin, CO, and ferritin [20,50,51,52,53,54], which are increased following (R)IPC [55,56,57,58]. Moreover, RIPC-mediated protection can act via various alternative signaling pathways, including humoral, neuronal, and systemic mechanisms [22,59].…”
Section: Resultsmentioning
confidence: 99%